Mechanistic Studies of Gypenosides in Microglial State Transition and its Implications in Depression-Like Behaviors: Role of TLR4/MyD88/NF-κB Signaling - Cao, Li-Hua; Zhao, Yuan-Yuan; Bai, Ming; Geliebter, David; Geliebter, Jan; Tiwari, Raj; He, Hong-Juan; Wang, Zhen-zhen; Jia, Xing-Yuan; Li, Jin; Li, Xiu-Min; Miao, Ming-San (Frontiers in Pharmacology, 2022)
Depression is a prevalent psychiatric disorder. Microglial state transition has been found in many neurological disorders including depression. Gypenosides (Gypenosides I-LXXVIII, Gps) are saponin extracts isolated from the traditional Chinese herb Gynostemma pentaphyllum (Thunb.) Makino that exert anti-inflammatory and neuroprotective activities and regulate depression-like behaviors. However, its effect on microglial state transition in depression remains unknown. We aimed to evaluate the potential relationship between Gps and TLR4/MyD88/NF-κB signaling in microglial state transition in vitro and in vivo. First, BV-2 cells (microglial cell line) were exposed to lipopolysaccharides (LPS) and treated with 10 or 5 μg/ml Gps. Second, the chronic unpredictable mild stress (CUMS)-induced depression mouse model was used to investigate the antidepressant-like behaviors effects of Gps (100 or 50 mg/kg). We determined depression-like behaviors using the open-field test (OFT), forced swim test (FST), and sucrose preference test (SPT). Proteins and inflammatory factors in the TLR4/MyD88/NF-κB signaling pathway and the different microglial reaction states markers were subsequently conducted using enzyme-linked immunosorbent assay, immunocytochemistry, immunofluorescence, qPCR, or Western blotting analyses to evaluate the anti-inflammatory and antidepressant properties of Gps and the underlying molecular mechanisms. We found that Gps regulated the microglial cell line state transition in LPS-exposed BV-2 cells, as evidenced by the significantly decreased expression of inflammatory parameters iNOS, IL-1β, IL-6, and TNF-α and significantly promoted anti-inflammatory microglial phenotypes markers CD206 (Mrc1) and IL-10. More importantly, Gps protected against the loss of monoamine neurotransmitters and depression-like behavior in a mouse model of depression, which was accompanied by a regulation of the microglial state transition. Mechanistically, Gps inhibited TLR4/MyD88/NF-κB signaling, which reduced the release of downstream inflammatory cytokines (IL-1β, IL-6, and TNF-α) and promoted microglial phenotype transition, which all together contributed to the antidepressant effect. Our results suggest that Gps prevents depression-like behaviors by regulating the microglial state transition and inhibiting the TLR4/MyD88/NF-κB signaling pathway. Thus, Gps could be a promising therapeutic strategy to prevent and treat depression-like behaviors and other psychiatric disorders.